2009
DOI: 10.1007/s11999-008-0477-z
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Morphology Due to Impingement Influences the Range of Motion in Slipped Capital Femoral Epiphysis

Abstract: Femoroacetabular impingement due to metaphyseal prominence is associated with the slippage in patients with slipped capital femoral epiphysis (SCFE), but it is unclear whether the changes in femoral metaphysis morphology are associated with range of motion (ROM) changes or type of impingement. We asked whether the femoral head-neck junction morphology influences ROM analysis and type of impingement in addition to the slip angle and the acetabular version. We analyzed in 31 patients with SCFE the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 21 publications
2
81
1
3
Order By: Relevance
“…unaffected hips and 11.9°to 15.7°for affected hips; these results are similar to ours [16,23,34]. Consistent with previous literature, our study did not demonstrate any difference in AV cen among affected hips, unaffected hips, and the normal control group, suggesting the retroversion found in AV sup is localized to the superior part of the acetabulum.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…unaffected hips and 11.9°to 15.7°for affected hips; these results are similar to ours [16,23,34]. Consistent with previous literature, our study did not demonstrate any difference in AV cen among affected hips, unaffected hips, and the normal control group, suggesting the retroversion found in AV sup is localized to the superior part of the acetabulum.…”
supporting
confidence: 92%
“…In contrast to Sankar et al [30], who used biplanar radiography and the crossover sign [29] to demonstrate acetabular retroversion, previous studies finding no relationship between acetabular retroversion and SCFE utilized two-dimensional (2-D) and three-dimensional (3-D) CT [16,23,34]. These CT-based studies evaluated acetabular retroversion based on only a single axial slice corresponding to the center of the femoral head.…”
Section: Introductionmentioning
confidence: 99%
“…The posterior wall sign was positive in 85 % of cases [26]. This is in contrast to Mamisch et al and Kordelle et al [27,28], who, in two separate studies, found no relationships between acetabular version and SCFE. Controversy remains concerning the existence of abnormal acetabular morphology in SCFE and whether it is a primary or secondary phenomenon.…”
Section: Bony Impingement-pathologymentioning
confidence: 95%
“…The remodeling process has been associated with 39% excellent and 50% good results assessed by the Heyman and Herndon criteria in a series of 44 patients followed for an average of 11.4 years [7]. Current investigations however have challenged remodeling as a benign process [42,54,69]. Using a three-dimensional modeling study, Rab [69] described two types of mechanical conflict between the femoral metaphysis and the acetabulum in the production of abnormal motion after SCFE.…”
Section: Search Strategies and Criteriamentioning
confidence: 99%